Cost-effectiveness analyses of self-harm strategies aimed at reducing the mortality of pesticide self-poisonings in Sri Lanka: a study protocol. Issue 2 (27th February 2015) - Madsen, Lizell Bustamante; Eddleston, Michael; Hansen, Kristian Schultz; Pearson, Melissa; Agampodi, Suneth; Jayamanne, Shaluka; Konradsen, Flemming
Abstract : Introduction: An estimated 803 900 people worldwide died as a result of self-harm in 2012. The deliberate ingestion of pesticides has been identified as the method most frequently used to commit fatal self-harm globally. In Sri Lanka, it is estimated that up to 60% of all suicides are committed using this method. The aim of the present study is to assess the cost-effectiveness of an ongoing safe storage intervention currently taking place in a rural Sri Lankan district and to model the cost-effectiveness of implementing the safe storage intervention as well as four potential interventions (legislative, medical management, follow-up contact and mobile phone contact) on a national level. Methods and analysis: Study design for all the strategies is a cost-effectiveness analysis. A governmental perspective is adopted. The time horizon for tracking the associated costs and health outcomes of the safe storage intervention on district level runs over 3 years. The time horizon is extended to 5 years when modelling a full national roll-out of the respective interventions. The discounting of costs and health outcomes are undertaken at the recommended real rate of 3%. Threshold analyses of the modelled strategies are employed to assess the strategies potential for cost-effectiveness, running scenarios with health outcome improvements ranging from 1% to 100%. Sensitivity analyses are also performed. The main outcome measures of the safe storage intervention are incremental cost-effectiveness ratios. Ethics and dissemination: Ethical approval was granted for the safe storage project from the University of Peradeniya, Sri Lanka, in March of 2008. An amendment for the present study was granted from Rajarata University of Sri Lanka in November of 2013. Findings will be disseminated to public and private stakeholders in local and national government in Sri Lanka as well as the wider academic audience through peer-reviewed publications and international conferences. Trial registration number: The safe storage cluster trial is registered with the Clinical Trials, ref: NCT1146496 (http://clinicaltrialsfeeds.org/clinical-trials/show/NCT1146496 ).